A computationally efficient non-coherent technique for wireless relay networks - Samer Alabed; Aymen I. Zreikat; Mohammad Al-Abed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This article introduces a full-rate differential distributed orthogonal space-time coding technique using the amplify-and-forward protocol. The proposed technique has a markedly low encoding and decoding complexity at all transmitting and receiving terminals. Furthermore, the method does not need either differential encoding or channel state information at any transmitting or receiving terminal where the information symbols are directly transmitted. Instead, the differential detection scheme is performed at the destination terminal. In our simulations, the performance of the suggested technique is performed by computer simulations in Rayleigh fading channel, using the amplify-and-forward protocol, to show that our proposed differential technique outperforms the corresponding reference techniques